2016
DOI: 10.1007/s40675-016-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares and Posttraumatic Stress Disorder (PTSD)

Abstract: Nightmares are a unique feature of posttraumatic stress disorder (PTSD). Although nightmares are a symptom of PTSD, they have been shown to independently contribute to psychiatric distress and poor outcomes, including heightened suicidality and suicide. Nightmares are often resistant to recommended pharmacological or psychological PTSD treatments. Fortunately, nightmare-specific treatments are available, and improvements in nightmares are associated with clinically significant improvements in sleep quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 51 publications
1
29
0
1
Order By: Relevance
“…This supports previous findings on medical staff from Wuhan, China, which showed that medical staff working in isolation unit had 1.71 times higher probability of reporting insomnia symptoms ( Zhang et al, 2020 ). Similarly, our findings showing higher incidences of nightmares among healthcare workers working at COVID-19 entry points support previous research that suggests nightmares present one of the symptoms of post-traumatic stress disorder ( Campbell and Germain, 2016 ; Rangachari and Woods, 2020 ), with healthcare workers working directly with COVID-19 patients reporting significantly more PTSD symptoms in comparison to other healthcare workers ( Johnson et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…This supports previous findings on medical staff from Wuhan, China, which showed that medical staff working in isolation unit had 1.71 times higher probability of reporting insomnia symptoms ( Zhang et al, 2020 ). Similarly, our findings showing higher incidences of nightmares among healthcare workers working at COVID-19 entry points support previous research that suggests nightmares present one of the symptoms of post-traumatic stress disorder ( Campbell and Germain, 2016 ; Rangachari and Woods, 2020 ), with healthcare workers working directly with COVID-19 patients reporting significantly more PTSD symptoms in comparison to other healthcare workers ( Johnson et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Though, it remains unclear whether dream content can distinguish between clinical disorders. Nightmares are especially relevant to mental health, featuring as a diagnostic symptom for posttraumatic stress disorder (Campbell and Germain, 2016), and a common correlate with schizophrenia (Okorome Mume, 2009), depression and anxiety (Swart et al, 2013), and personality disorders (Schredl et al, 2012). Nightmare frequency and intensity have been positively correlated with incidence of suicidal thoughts and behaviors (Bernert et al, 2005), suggesting nightmares could be a near-term risk factor to assess during crisis.…”
Section: Relevant Research On Mental Health and Text Analysismentioning
confidence: 99%
“…For example, nightmares are associated with elevated heart rate ( Fisher, Byrne, Edwards, & Kahn, 1970 ) and increased eye movements and respiration rate (‘high anxiety dreams’; Goodenough, Witkin, Koulack, & Cohen, 1975 ), which suggests the body is physically experiencing a nightmare as long as the mind is. This view has substantial implications for Posttraumatic Stress Disorder (PTSD) where patients re-experience a trauma during nightmares ( Van der Kolk, 1994 ), leading authors to claim that ‘dreams themselves could be traumatic for the dreamer’ ( Campbell & Germain, 2016 ). Here, we expand on the argument for a stronger role of dreaming in sleeping physiology than has previously been acknowledged and, subsequently, explore the functional implications of this claim.…”
Section: Introductionmentioning
confidence: 99%